PENINGKATAN HASIL TANAMAN KANGKUNG DARAT (Ipomoea reptans, L.) MELALUI PERLAKUAN JARAK TANAM DAN JUMLAH TANAMAN PER LUBANG - Raditya Febriyono; Yulia Eko Susilowati; Agus Suprapto (JURNAL VIGOR, 2017)
An experiment of the effect of plant distance and umber plant per hole of water spinaches (Ipomoea reptans L.) had been done since Pebruari 2016 until April 2016 in Krajan II, Soropadan Village, District Pringsurat, Temanggung regency. The height of 530 m above sea level research, latosol soil type and pH 6. The method of experiment used was factorial (3 x 4) with a randomized completly 3 block design, consist of three replications. The first factor is a plant spacing 5 cm x 5 cm, 5 cm x 10 cm, and 5 cm x 15 cm. The second factor is the number of plants per hole 1 plant, 2 plants, 3 plants and 4 plants. The results showed that the plant distance increase the yield fresh weight of root  at planting 1, 2, 3 and harvest indek at planting 1, 2. The number of plants per hole increase the yield fresh weight of plants for planting 1, 2, 3, dry weight of root at planting 2 and harvest indek at planting 1. The combination of plant distance and number of plant per hole no interaction at all parameters.